Adaptation and Perception. (9th July 2018) - Nicklas, Pascal; Baumbach, Sibylle
Abstract: Recognizing that a work of art is an adaptation changes the perception of it entirely and makes it possible to perceive it as an adaptation. Adaptations are a very specific kind of art experience in physiological, cultural, and medial respects: the palimpsestuous structure of presence and absence requires modes of processing involving feedback loops of memory and perception, cultural mechanisms involved in the processes of selective perception and medial underpinnings of the presentation of adaptations influencing and defining ways of perceiving them. There is a multitude of approaches to the very under-researched topic of adaptation and perception which is outlined here with a view to inspiring further research.